2021
DOI: 10.1523/jneurosci.2420-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Signaling Disengages Feedforward Transmission in the Nucleus Accumbens Shell

Abstract: The nucleus accumbens shell (NAcSh) receives extensive monoaminergic input from multiple midbrain structures. However, little is known how norepinephrine (NE) modulates NAc circuit dynamics. Using a dynamic electrophysiological approach with optogenetics, pharmacology, and drugs acutely restricted by tethering (DART), we explored microcircuit-specific neuromodulatory mechanisms recruited by NE signaling in the NAcSh of parvalbumin (PV)-specific reporter mice. Surprisingly, NE had little direct effect on modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…It seems, that the noradrenergic pathways innervating the striatal subfield, i.e. the NAcc shell, originating mainly from the A1 and A2 regions (Delfs et al 1998;Manz et al 2021), which could not be damaged by the unilateral administration of 6-OHDA into the left MFB, played a significant role in increasing the NA content in the ipsilateral STR. Thus, DES when administered in combination with L-DOPA could increase the level of NA, due to inhibition of its reuptake by NET at the terminals of the ascending noradrenergic pathways from regions A1 and A2, but it cannot be ruled out that L-DOPA itself could serve as a substrate for NA synthesis in these terminals, increasing the total NA pool in the ipsilateral STR.…”
Section: Impact Of Des and L-dopa On Motor Functionsmentioning
confidence: 99%
“…It seems, that the noradrenergic pathways innervating the striatal subfield, i.e. the NAcc shell, originating mainly from the A1 and A2 regions (Delfs et al 1998;Manz et al 2021), which could not be damaged by the unilateral administration of 6-OHDA into the left MFB, played a significant role in increasing the NA content in the ipsilateral STR. Thus, DES when administered in combination with L-DOPA could increase the level of NA, due to inhibition of its reuptake by NET at the terminals of the ascending noradrenergic pathways from regions A1 and A2, but it cannot be ruled out that L-DOPA itself could serve as a substrate for NA synthesis in these terminals, increasing the total NA pool in the ipsilateral STR.…”
Section: Impact Of Des and L-dopa On Motor Functionsmentioning
confidence: 99%
“…While norepinephrine’s role in sensory processing is understudied, recent work has begun to examine its role in reward-related tasks. In particular, recent evidence suggests that norepinephrine plays a role in modulating glutamatergic synapses in the nucleus accumbens, and that it might tune feedforward inhibition and impact reward-related circuitry as well as motivational states ( Manz et al, 2021 ). Animal studies have also suggested that norepinephrine is associated with the amount of effort required to perform a reward task (here, force exerted on a grip in order to receive a reward) and that this effort is distinct from reward sensitivity ( Varazzani et al, 2015 ; Borderies et al, 2020 ).…”
Section: Antidepressant Drugs and Predictive Processesmentioning
confidence: 99%
“…PV tdT cells in the NAcc were visualized using Scientifica PatchVision software via 530 nm LED light. PV-FSIs were confirmed according to biophysical properties (capacitance, membrane resistance, and AMPAR decay kinetics) [11,17].…”
Section: Electrophysiologymentioning
confidence: 99%
“…For example, inhibition of NAc PV-FSIs increases impulsivity and decreases psychostimulant induced associative learning [14,15]. Studies from our lab and others indicate that feedforward glutamatergic synapses onto PV-FSIs exhibit multiple molecularly distinct modes of plasticity, each proceeding via Gprotein-coupled receptor (GPCR)-dependent mechanisms [10,11,16,17]. However, it is unknown whether endogenous opioid signaling, a neuromodulatory system critically involved in adaptive and pathological reward behavior, modulates PV-FSIembedded feedforward microcircuits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation